Czy płeć twórcy ma znaczenie? Przekonania nauczycieli na temat charakterystyki kreatywnego chłopca oraz kreatywnej dziewczynki = Does the gender of the creator matter? Teacher`s beliefs about the characteristics of a creative boy and a creative girl - Gralewski, Jacek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Despite the lack of documented differences in the intensity of creative abilities between women and men, the observed disproportion between men and women in terms of creative achievements may result from different socialization and education paths of boys and girls. The purpose of the article is to compare teachers` beliefs about the characteristics of a creative boy and a creative girl. 128 experienced kindergarten and elementary school teachers were involved in the study.
Keywords: twórczość; przekonania nauczycieli; ukryte teorie twórczości; creativity; teachers` beliefs; hidden theories of creativity